Correlation of Proton Pump Inhibitors with Pulmonary Tuberculosis: A Case-Control Study in Taiwan - Cheng, Kao-Chi; Liao, Kuan-Fu; Lin, Cheng-Li; Lai, Shih-Wei (Frontiers in Pharmacology, 2017)
Background and Objectives. Although the relationship between the use of proton pump inhibitors (PPIs) and pulmonary tuberculosis (TB) in Taiwan published in 2014. Due to just only one article and not enough comprehensively, we explore this issue. Methods. We conducted a population-based case-control study to identify 9422 subjects aged 20 years or older with newly diagnosed pulmonary TB in 2000–2013 as test cases. We then randomly selected 9422 subjects aged 20 years or older without pulmonary TB as controls. Both cases and controls were matched in terms of sex, age, and comorbidities. Use of PPIs were defined as subjects who had had at least one prescription for these medications before the index date. No use was defined as subjects who had never had a prescription for PPIs before the index date. The odds ratio (OR) and 95% confidence interval (CI) for pulmonary TB associated with PPI use was estimated using the logistic regression model. Results. The OR of pulmonary TB was 1.31 for subjects who had used PPIs (95% CI 1.22, 1.41) compared with those with no use of the medications. Sub-analysis revealed the OR of pulmonary TB in subjects using PPI per increasing microgram was 1.25 (95% CI 1.19, 1.30). Conclusions. PPI use is associated with a 1.3-fold increase in odds of developing pulmonary TB in Taiwan. There is a dose-related response between PPI use and pulmonary TB.